Influence of heat treatment on mechanical properties and precipitation kinetic of sugar palm fiber ash reinforced LM26 AI matrix composites - Aliyu, Isah; Sapuan Salit, Mohd; Zainudin, Edi Syams; Mohamed Yusoff, Mohd Zuhri; Yahaya, Ridwan (Universiti Putra Malaysia, 2023)
Heat treatment is a commonly known treatment subjected to aluminum alloy and their composites to improve their mechanical properties for automotive, aerospace, and marine applications. The heat treatment was carried out to determine the influence of aging time and temperature on the mechanical properties of LM26 Al alloy reinforced with 0, 2, 4, 6, 8, and 10 wt% sugar palm fiber ash (SPFA) and its precipitation kinetics. The LM26 Al/SPFA composites were fabricated through the stir casting technique, solutionized at 500oC for 2 h, and quenched in water at room temperature. The quenched composites were aged at various ageing times and temperatures and allowed to air cool. The hardness, impact energy, tensile, and compression strengths of the aged composites were appraised. In addition, the precipitation kinetics were studied to validate the precipitation temperatures of LM26 Al matrix composites. The hardness of the composites increased with aging time and temperature, with LM26 Al/10 wt% SPFA composite reaching a hardness peak of 102.10 VH at an aging temperature of 180oC after 5 h, compared to 56.70 VH for LM26 Al alloy. Similarly, after 5 h of aging at 180oC, the LM26 Al/8 wt% SPFA composite achieved maximum tensile and compression strengths of 198.21 MPa and 326.22 MPa, respectively. Precipitation temperature decreased from 584.8oC (LM26 Al alloy) to 480.46oC (LM26/ 10wt% SPFA), indicating that adding SPFA improved precipitation kinetics. The age-hardened composite with high hardness, tensile strength, and compression strength makes it a promising piston material application in the automotive industry.